2021
DOI: 10.1002/ptr.7050
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of possible interactions for herbal medicines and dietary supplements used concomitantly with disease‐modifying or symptom‐alleviating multiple sclerosis drugs

Abstract: Multiple Sclerosis (MS) is a demyelinating disease affecting the central nervous system, with no curative medicine available. The use of herbal drugs and dietary supplements is increasing among people with MS (PwMS), raising a need for knowledge about potential interactions between conventional MS medicine and herbal drugs/ dietary supplements. This systematic review provides information about the safety of simultaneous use of conventional MS-drugs and herbal drugs frequently used by PwMS. The study included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 138 publications
(179 reference statements)
0
7
0
Order By: Relevance
“… 21 , 22 Thus, the possibility of pharmacologic interactions is high. 23 CBD and THC affect common targets for drug metabolism (such as cytochrome P450 [CYP]3A4/2C19 enzymes), which may affect the pharmacokinetics/pharmacodynamics of other drugs that interact with these pathways. 24 , 25 CBD or marijuana use decreases clearance of drugs and their metabolites that use CYP2C19 (e.g., warfarin), increases clearance of CYP1A2-metabolized drugs, and may result in adverse additive effects in combination with sympathomimetics (e.g., hypertension), alcohol and opioids (e.g., ataxia), and anticholinergics (e.g., tachycardia).…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 Thus, the possibility of pharmacologic interactions is high. 23 CBD and THC affect common targets for drug metabolism (such as cytochrome P450 [CYP]3A4/2C19 enzymes), which may affect the pharmacokinetics/pharmacodynamics of other drugs that interact with these pathways. 24 , 25 CBD or marijuana use decreases clearance of drugs and their metabolites that use CYP2C19 (e.g., warfarin), increases clearance of CYP1A2-metabolized drugs, and may result in adverse additive effects in combination with sympathomimetics (e.g., hypertension), alcohol and opioids (e.g., ataxia), and anticholinergics (e.g., tachycardia).…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 22 To maintain quality of life and improve functional outcomes, many patients seek additional help in the use of complementary and alternative medicines (CAM) such as dietary supplements or herbal drugs. 23 25 It was reported that 67% to 80% of MS patients use CAM and half of them even as an alternative to conventional therapies. 26 , 27 For example, vitamin D supplementation is often part of a nutritional health plan because low cholecalciferol levels in serum have been associated with a higher risk of relapses.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper is based on a larger sequential explanatory mixed methods study, carried out from February 2019 to June 2020. The study consisted of a cross-sectional survey [8], a systematic literature review [16] and qualitative in-depth interviews. The results shared in this paper are based on data from the interviews, the primary aim of which was to explore information-seeking behavior among PwMS related to their use of DIHES.…”
Section: Methodsmentioning
confidence: 99%